Learning Arabic Using Moodle Application Based E-Learning for Madrasah Aliyah│Pembelajaran Bahasa Arab dengan Menggunakan E-Learning Berbasis Aplikasi Moodle untuk Madrasah Aliyah - Lilis Dwi Andarwati; Erlina; Koderi; Sulthan Syahril (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Moodle Based E-Learning in Arabic Language Learning can increase students' interest in learning. This study aims to produce e-learning based learning media with moodle applications. This research is a type of research and development research using the ADDIE (analysis, design, development, implementation and evaluation). The data in this study were obtained through questionnaires, interviews, observation and documentation. Questionnaires were given to class X MA Al Ma'ruf Margodadi students, interviews were conducted with teachers and several students, observations were made in class during product trials, then documentation was obtained from student learning out comes. Then to test the feasibility of the product the researcher got help from the validators in this study were material experts, media experts, and Arabic subject teachers. The data collection method in this study used pre-test and post-test data. The statistical analysis used to analyze the pre-test and post-test data is the T-test. The results of this study are: The process of developing e-learning media based on the Moodle application for learning Arabic in class X in odd semesters.The feasibility results of the developed media are very feasible with a percentage of 84% by material experts, and very feasible with a percentage of 95% by media experts and 89% by Arabic teacher experts. The students' response to the developed media is very feasible with a percentage of 85% The effectiveness of the product can be seen from the average pre-test (preliminary test) score of students of 65.294 and the average post-test (final test) score of 80.882 with a student progress score of 15.588 with the results of the T-test analysis t 0 = 8.89 > t.table = 1.66. It can be concluded that the e-learning media based on the Moodle application for learning Arabic class X which was developed is very feasible and very effective for learning Arabic.